Solvents, Ionic Liquids and Solvent Effects 2020
DOI: 10.5772/intechopen.87151
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Dye Sensitizers Derived from Anthocyanidins for Applications in Photocatalysis

Abstract: Anthocyanidins under the effects of solvents water, ethanol, n-hexane, and methanol are interesting due to their suitability as natural dyes for photocatalytic applications. In this chapter, DFT and TDDFT methodologies are used to study their electronic structure. The results displayed include HOMO, LUMO, HOMO-LUMO gap, chemical properties, and reorganization energies for the ground states, and excited state data are also displayed. Malvidin in gas phase has lower gap energy. After addition of solvents, gap en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The lowest energy absorption in these molecules is due to the transition from HOMO to LUMO with the largest oscillator strength resulting in an enhanced LHE, this approach emphasizes the parameters recommended in the literature to identify the best choice [41,47,48]. Cyanidin, malvidin, and peonidin data has been regenerated for this work with very similar results, considering there is a set of our own results obtained with different methodology that were published previously elsewhere [22]. *Experimental data from the literature [43].…”
Section: Excited States With Tddftmentioning
confidence: 64%
See 4 more Smart Citations
“…The lowest energy absorption in these molecules is due to the transition from HOMO to LUMO with the largest oscillator strength resulting in an enhanced LHE, this approach emphasizes the parameters recommended in the literature to identify the best choice [41,47,48]. Cyanidin, malvidin, and peonidin data has been regenerated for this work with very similar results, considering there is a set of our own results obtained with different methodology that were published previously elsewhere [22]. *Experimental data from the literature [43].…”
Section: Excited States With Tddftmentioning
confidence: 64%
“…The difference between HOMO-LUMO is generally accepted as a similar value to the band gap. Results for HOMO-LUMO gap were between 2.539 and 2.881 eV in the *Data regenerated by our research group with a similar theoretical method reported elsewhere [22].…”
Section: Electronic Structurementioning
confidence: 76%
See 3 more Smart Citations